DEVELOPING WORD WALL AS MEDIA IN TEACHING WRITING SKILLS ON DESCRIPTIVE TEXT FOR THE SEVENTH GRADE STUDENTS AT SMP YPI AMIR HAMZAH MEDAN - Ade Riska Damayanti; Masitowarni Siregar; Puan Suri Mira Annisa Sembiring (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2020)
The study was aimed to to develop learning media in Writing Descriptive Text for Grade VII of Junior High School Students. This study was conducted by using Research and Development (R&D) design through six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product. The subject of the study was Grade VII of SMP Ypi Amir Hamzah Medan. The instruments of data collection were gathered  by administring interview and distributing questionnaire. The study conducted interview to the English teacher and distributing questionnaire to 25 respondents to get the students’ needs. The interview and questionnaire results proved that the students need English learning media which can motivate the students to understand about writing descriptive text. The product had been validated by the experts namely English lecturer and English teacher. The product result was Word Wall which is modifying House based on destination of North Sumatera. The result of experts’ validation showed that the media was an appropriate media to be used on writing descriptive text by getting the average percentage 92% categorized excellent.Keywords: Writing, Descriptive Text, Word Wall, Research and Development